The Role of the Innate Immune System in the Development of Postcovid Syndrome and its Complications - V. N. Larina; E. A. Stodelova; Zh. M. Salmasi; A. N. Kazimirskij; G. V. Porjadin (SINAPS LLC, 2023)
To date, the problem of preserving symptoms after recovery from a new coronavirus infection is urgent in the world. This condition is called postcovid syndrome. The clinical picture of postcovid syndrome has multiple manifestations: general, respiratory, cardiovascular, gastrointestinal, skin and other symptoms. At the moment, there are no laboratory criteria for the diagnosis of this condition, but the great role of neutrophils in the development of both acute disease and postcovid syndrome has been proven. The formation of neutrophil extracellular traps (not toz) is one of the pathophysiological mechanisms of the course of a new coronavirus infection. In addition, the effect of the ketosis process on the development of complications in the postcovid period has been proven. The article discusses the history of the term, various clinical manifestations of the postcovid period, as well as the role of innate immunity mechanisms at all stages of the course of a new coronavirus infection.